Pandora's box - Saunders, Nick. (Milwaukee, WI : World Almanac Library, 2007)
Presents a graphic novel that tells the ancient Greek legend of Pandora and the chaos she unleashes when she opens up the mysterious box.
Includes bibliographical references (p. 47) and index.
School Library Journal.
3.1
5-8
Keywords: Pandora (Greek mythology) -- Comic books, strips, etc. -- Juvenile literature; Cartoons and comics; Mythology, Greek -- Cartoons and comics; Pandora (Greek mythology) -- Cartoons and comics; Comic books, strips, etc; Greek mythology -- Comic books, strips, etc; Pandora (Greek mythology) -- Comic books, strips, etc